2018
DOI: 10.1096/fj.201701456rr
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori‐induced miR‐135b‐5p promotes cisplatin resistance in gastric cancer

Abstract: Helicobacter pylori infection is a major risk factor for the development of gastric cancer. Aberrant expression of microRNAs is strongly implicated in gastric tumorigenesis; however, their contribution in response to H. pylori infection has not been fully elucidated. In this study, we evaluated the expression of miR-135b-5p and its role in gastric cancer. We describe the overexpression of miR-135b-5p in human gastric cancer tissue samples compared with normal tissue samples. Furthermore, we found that miR-135b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…Helicobacter pylori has been acknowledged to be one of the most important pathogenic factors for GC [42]. It has also been reported that H. pylori can regulate CDDP resistance [43,44]. Nevertheless, many of the patients did not receive H. pylori examination, so we did not analyze the relationship between H. pylori and circMCTP2.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori has been acknowledged to be one of the most important pathogenic factors for GC [42]. It has also been reported that H. pylori can regulate CDDP resistance [43,44]. Nevertheless, many of the patients did not receive H. pylori examination, so we did not analyze the relationship between H. pylori and circMCTP2.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional first-line chemotherapy with platinum-based drugs is still the main regimen for gastric cancer [20,21]. Although it is effective, its prominent disadvantages are severe side effects and drug resistance after repeated use [22,23]. However, the emerging peptide drugs have the advantages of small molecular weight, strong tissue permeability, low immunity, high affinity with the target and few side effects [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-421, a highly expressed miRNA in advanced gastric cancer patients, could also promote gastric cancer metastasis and DDP resistance through inhibiting E-cadherin and caspase-3 expression, in vivo and in vitro [91]. In addition, oncogenic miR-135b-5p, miR-135b, miR-17-5p, miR-193a-3p, miR-4295 and miR-3174 confer DDP resistance of gastric cancer cells through silencing Krüppel-like factor 4 (KLF4), mammalian ste20-like kinase 1 (MST1), p21, SRSF2, leucine-rich repeats and immunoglobulin-like domains 1 (LRIG1) and ARHGAP10, respectively [28,[92][93][94][95][96]. For oxaliplatin resistance, the oncogenic miR-27a has been found to enhance MDR properties by inducing MDR1/P-gp, lung resistance protein (LRP) and Bcl-2 expression in gastric cancer [97].…”
Section: Mirnas and Resistance To Platinum Drugsmentioning
confidence: 99%